Application of OXITEST for Prediction of Shelf-Lives of Selected Cold-Pressed Oils - Tsao, Chieh-Hsi; Chang, Chih-Wei; Ho, Yu-Chi; Chuang, Yung-Kun; Lee, Wei-Ju (Frontiers in Nutrition, 2021)
Introduction: Due to the enhanced awareness of consumers concerning healthy foods, homemade expeller-pressed oils have become popular worldwide. However, an extended storage period may lead to oxidization of the oil and exposure to hazardous byproducts by consumers. Methods: In this study, ten pressed oil samples prepared from common oilseeds using a small-scale expeller oil press were analyzed by OXITEST with a sample amount of 5 g of oil and an oxygen pressure of 800 kPa under accelerated conditions for shelf-life projections. The oil properties were investigated, including the recovery, smoke point, acid value, iodine value, and fatty acid composition. Results: The autoxidation reaction of various expeller-pressed oils under an accelerated testing system followed zero-order Arrhenius kinetics (R2 > 0.99). Shelf-lives of the pressed oils at 25 °C were estimated by extrapolation to range 105 1089 days. The obtained shelf-lives were significantly correlated with log induction period (IP) values (r > 0.81, p < 0.05) and unsaturated fatty acids (UFAs) (r < -0.69, p < 0.05), but not with the iodine value, acid value, or smoke point. Scatter diagrams between shelf-lives and UFAs suggested that these pressed oils could be grouped by two linear regression curves (r > 0.98, p < 0.05). The predictive equations using multiple linear regression are presented herein, with predictor variables of UFAs and an unspecified item involving potential influencing factors such as tocopherol contents (r > 0.88, p < 0.05). Conclusions: Our findings first revealed that the UFA portion was partially correlated with the shelf-lives of selected expeller-pressed seed oils as estimated by the OXITEST. The derived equations can be applied for shelf-life predictions of expeller-pressed oils stored under dark ambient conditions based on the fatty acid profile.